Corporate Internal Communication - SharePoint and document sharing platform - Foltýnová, Klára (2017)
This thesis provides recommendations on the content, structure, features and functionalities of the Customer Knowledge Management Platform in Hilti to enable Customers & Insights Team to share insights with stakeholders. The theoretical part reviews the most relevant previous findings regarding general communication, corporate communication, information management process and technological platforms used. The practical part describes the status quo of internal communication in Hilti including communication channels and knowledge, information and document sharing. The theoretical part consists of qualitative part which provides actionable recommendations on the content and structure of the platform and of quantitative part which focuses on desired features and functionalities of the platform. Results show that the requirements of the platform differ between the potential users and administrators and suggests ways how to satisfy both groups.